A case study of an iron-deficient Female Olympic 1500-m Runner - Pedlar, C. R.; Whyte, G. P.; Burden, R.; Moore, B.; Horgan, G.; Pollock, N. (International Journal of Sports Physiology and Performance, 2013)
This case study examines the impact of low serum ferritin (sFe) on physiological assessment measures and performance in a young female 1500-m runner undertaking approximately 95-130 km/wk training. The study spans 4 race seasons and an Olympic Games. During this period, 25 venous blood samples were analyzed for sFe and hemoglobin (Hb); running economy, VO2max), and lactate threshold were measured on 6 occasions separated by 8-10 mo. Training was carefully monitored including 65 monitored treadmill training runs (targeting an intensity associated with the onset of blood lactate accumulation) using blood lactate and heart rate. Performances at competitive track events were recorded. All data were compared longitudinally. Mean sFe was 24.5 ± 7.6 µg/L (range 10-47), appearing to be in gradual decline with the exception of 2 data points (37 and 47 µg/L) after parenteral iron injections before championships, when the lowest values tended to occur, coinciding with peak training volumes. Each season, 1500-m performance improved, from 4:12.8 in year 1 to 4:03.5 in year 4. VO2max) (69.8 ± 2.0 mL /kg· min) and running economy (%VO2max) at a fixed speed of 16 km/h; max 87.8%, min 80.3%) were stable across time and lactate threshold improved (from 14 to 15.5 km/h). Evidence of anemia (Hb <12 g/dL) was absent. These unique data demonstrate that in 1 endurance athlete, performance can continue to improve despite an apparent iron deficiency. Raising training volume may have caused increased iron utilization; however, the effect of this on performance is unknown. Iron injections were effective in raising sFe in the short term but did not appear to affect the long-term pattern.